2019 IEEE 58th Conference on Decision and Control (CDC) 2019
DOI: 10.1109/cdc40024.2019.9029955
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Identification of Linear Evolutions in Nonlinear Vector Fields: Koopman Invariant Subspaces

Abstract: This paper presents a data-driven approach to identify finite-dimensional Koopman invariant subspaces and eigenfunctions of the Koopman operator. Given a dictionary of functions and a collection of data snapshots of the dynamical system, we rely on the Extended Dynamic Mode Decomposition (EDMD) method to approximate the Koopman operator. We start by establishing that, if a function in the space generated by the dictionary evolves linearly according to the dynamics, then it must correspond to an eigenvector of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…When the number of features is larger than the number of data snapshots, EDMD eigenvalues can be misleading (Otto & Rowley 2019) and often plagued with spurious eigenfunctions that do not evolve linearly even when the number of data snapshots is sufficient. Analytically, it is clear that a Koopman eigenfunction in the span of the dictionary will be associated with one of the eigenvectors obtained from EDMD, given Ψ x is full rank, and contains sufficient snapshots M (Haseli & Cortés 2019). Indeed, the EDMD is an L 2 projection of the Koopman operator under the empirical measure (Korda & Mezić 2018b).…”
Section: Mode Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the number of features is larger than the number of data snapshots, EDMD eigenvalues can be misleading (Otto & Rowley 2019) and often plagued with spurious eigenfunctions that do not evolve linearly even when the number of data snapshots is sufficient. Analytically, it is clear that a Koopman eigenfunction in the span of the dictionary will be associated with one of the eigenvectors obtained from EDMD, given Ψ x is full rank, and contains sufficient snapshots M (Haseli & Cortés 2019). Indeed, the EDMD is an L 2 projection of the Koopman operator under the empirical measure (Korda & Mezić 2018b).…”
Section: Mode Selectionmentioning
confidence: 99%
“…This is effectively a recursive implementation of EDMD. Recently, Haseli & Cortés (2019) showed that given a sufficient amount of data, if there is any accurate Koopman eigenfunction spanned by the dictionary, it must correspond to one of the obtained eigenvectors. Moreover, they proposed the idea of mode selection by checking if the reciprocal of identified eigenvalue also appears when the temporal sequence of data is reversed, which is similar to the idea of comparing eigenvalues on the complex plane from different trajectories, as proposed by Hua et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Besides simplicity, using the Koopman linear representation for control can in certain cases also outperform feedback policies that are based on the underlying nonlinear dynamics [28], [29]. However, unless finite-dimensional Koopman invariant subspaces exist [28], [30], [31], the operator is infinitedimensional and renders practical use challenging. Studies seek finite-dimensional approximations using methods such as the Dynamic Mode Decomposition (DMD) [32] extended DMD (EDMD) [33], [34], Hankel-DMD [35], or closedform solutions [36], [37] which use state measurements to approximate Koopman operators.…”
Section: B Benefits and Applications Of Koopman Operatorsmentioning
confidence: 99%
“…Here, we gather some important results from [22], [31] regarding the SSD algorithm and its output. (A.…”
Section: Appendix a Properties Of The Symmetric Subspace Decompositio...mentioning
confidence: 99%
“…The next result shows that the eigendecomposition of K SSD captures all the functions in the span of the original dictionary that evolve linearly in time according to the available data. Theorem A.3: (Identification of Linear Evolutions using the SSD Algorithm [31]): Under Assumption 3.1, K SSD w = λw for some λ ∈ C and w ∈ C cols(KSSD)\{0} if and only if there…”
Section: Appendix a Properties Of The Symmetric Subspace Decompositio...mentioning
confidence: 99%